An evaluation study on amalgamation and performance of fiber reinforced concrete frames with infills and without infills. (2021) - Sivakumar, N.; Ananthi, G. Beulah Gnana; Deepak, M.S.
Abstract: This is an analysis of the quality of framed structures strengthened by using toughened fibre reinforced concrete which undergoes a lateral cyclic force. A measure of 1/3rd scale model frames were designed with infills and without infills and tested. The capacity design criteria serves as the base for moment resisting frames – i.e., the columns should be stronger than the beams to decrease early failure in concrete. Cubical, cylindrical and prism companion specimen were cast for hybrid fiber dosages of 0%, 0.5%, 1%, 1.5% and 2%, These were cured appropriately and the strength was examined for a period of 1 week and 4 weeks respectively. For this a simple frame with concrete grade of M25 was adopted. Polyolefin and compressed steel fibers in different proportions were used in this analysis. At the plastic hinge zone hybrid fibers of 0.5%, 1%, 1.5% and 2% were used. The viability of concrete mix was increased by adding super plasticizer in appropriate proportions. Totally 5 frames were cast and tested. A comparison of results of frames reinforced with hybrid fibers and the frame made of controlled concrete was made. The result showed, Hybrid/Amalgamated, Fibre strengthened concrete frames had higher ductility performance during cyclic loads.